Respiratory function and effects of SO2: 4-year follow up of Miyakejima residents after returning to the island. (19th October 2011) - Kochi, Takeshi; Iwasawa, Satoko; Nakano, Makiko; Michikawa, Takehiro; Uemura, Takamoto; Tsuboi, Tazuru; Yamada, Mutsuko; Kitamura, Hiroko; Wilson, Donald; Tanaka, Shigeru; Omae, Kazuyuki
Abstract : Objectives: Mount Oyama on Miyakejima Island, Tokyo, erupted in June, 2000. All Miyake village citizens were forced to evacuate from the island in September, 2000, due to continuous eruptions and emissions of unsafe amounts of volcanic gas, mainly SO2. From February, 2005, residents started to return to the island despite the fact that volcanic gas was still being emitted. This study examines changes in respiratory function over 4 years from autumn 2004 to November 2008. Methods: The study population comprised 276 adults (122 male, 154 female) who each underwent an examination for respiratory health just before returning to the island (2004) and another examination 4 years after their return (2008). Exposure was approximated by monitoring data across 7 monitoring stations. Mean SO2 concentration from February 2005 to November 2008 was 0.022 ppm. Effects were evaluated by spirometry. Results: Study subjects showed no reduction in lung function between 2004 and 2008. Conclusions: No change was observed in respiratory function in adult Miyakejima residents due to 4 years of residence in an environment with an average SO2 concentration of 0.022 ppm. However, to truly shed light on the effects of SO2 on respiratory function in adults, it is important to continue this study and conduct further analysis.